(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The study aims to show the impact of free cash flows on the value of the facility in Almarai, with recommendations that contribute to improving cash management and enhancing the value of the facility. The results of the statistical analysis showed that it was not possible to formulate an accurate model due to the absence of statistical significance in both models, which indicates the need to take into account additional factors, such as operating profits and financial structure, to explain the value of the facility more comprehensively. Accordingly, the study recommends expanding the scope of the research to include additional variables, such as operating profits and debt ratios, to enhance the accuracy of the models used and achieve a deeper understanding of the factors affecting the value of the facility.